Egyházi-világi hatalmi harc Zsarnay Lajos szemével - Marianna BÁTORINÉ MISÁK (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2019)
The Debates of Clerics and Laymen in the Church-governance Through the Eyes of Lajos Zsarnay.